Community of Believers of ‘Holy Men’ and ‘Saints’ or Community of Muslims? The Rise and Development of Early Muslim Historiography - Elad, Amikam (Journal of Semitic studies, 2002)
This study is an extended review article of Donner's Narratives of Islamic Origins . It will be composed of three sections: 1) a critical survey of the contents of the book, 2) some reservations with regard to a number of the topics Donner raises, and 3) comments and corrections.